The Effectiveness of Group Counseling with Cognitive Behavior Therapy (CBT) Approach to Improve Prisoners’ Emotion Regulation and Reduce Prisoners’ Anxiety (Universitas Negeri Semarang, 2019)
The aim of this study was to determine the effectiveness of group counseling with Cognitive Behavior Therapy to improve emotion regulation and reduce the anxiety of prisoners of Lapas Perempuan Semarang. The instrument used for this study was emotion regulation scale and anxiety scale. Meanwhile, there were 6 subjects involved in this study. In addition, the study employed pretest and multiple posttest design. The analysis results showed that there was an improvement in emotion regulation, and reduction in anxiety after the group counseling was conducted. These findings showed that group counseling with CBT approach was effective to improve emotion regulation and reduce the prisoners’ anxiety. However, in the follow-up assessment, it was found that the prisoners’ anxiety tended to improve again, so there was a significant difference in anxiety between pretest and follow-up. At last, the findings of this study provide initial proof that changes in anxiety level are not always in line with emotion regulation.